2021
DOI: 10.1177/00034894211025411
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Isotonic Seawater Nasal Spray Containing Chamomile Liquid Extract and Other Isotonic Seawater Nasal Washing Solutions for Allergic Rhinitis

Abstract: Objective: We aim to demonstrate the effect of an isotonic seawater spray containing chamomile liquid extract on symptoms and nasal mucociliary clearance in patients with allergic rhinitis by comparing it with other isotonic seawater nasal washing solutions. Methods: The study included 123 patients. Based on Allergic Rhinitis and its Impact on Asthma guidelines, mometasone furoate intranasal spray treatment was started for all patients in the group diagnosed with allergic rhinitis. In addition to this treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…It is used to treat hay fever, inflammation, muscle spasms, menstrual disorders, insomnia ulcers, wounds, gastrointestinal disorders, rheumatic pain, and hemorrhoids ( Srivastava et al, 2010 ). A recent study has shown that presence of chamomile extract in the isotonic seawater spray served as a good alternative treatment option for patients with hay fever ( Atar et al, 2022 ). The main constituents contributing to chamomile’s therapeutic potential are terpenoids (chamazulene and bisabolol) and flavonoids (apigenin, luteolin, and quercetin) ( Kolanos and Stice, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is used to treat hay fever, inflammation, muscle spasms, menstrual disorders, insomnia ulcers, wounds, gastrointestinal disorders, rheumatic pain, and hemorrhoids ( Srivastava et al, 2010 ). A recent study has shown that presence of chamomile extract in the isotonic seawater spray served as a good alternative treatment option for patients with hay fever ( Atar et al, 2022 ). The main constituents contributing to chamomile’s therapeutic potential are terpenoids (chamazulene and bisabolol) and flavonoids (apigenin, luteolin, and quercetin) ( Kolanos and Stice, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The main characteristics of the 29 included published articles are presented in S1-S3 Tables in S5 Appendix according to their PICO elements. Almost all [ 23 50 ] were conducted in adult populations while only one study [ 51 ] investigated the effects of medicinal plants among children. Of the 29 included studies, more than half reported a study duration of 28 days or longer.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies [ 23 , 24 , 26 , 36 , 47 , 50 ] compared medicinal plants and conventional treatment combined against conventional treatment only.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations